Suggested Curriculum Guide in Language Arts - Gadsden County Board of Public Instruction, Quincy, FL.; Gadsden County Board of Public Instruction, Quincy, FL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
GRADES OR AGES: Grades 1-12. SUBJECT MATTER: Language arts. ORGANIZATION AND PHYSICAL APPEARANCE: The guide is divided into four sections, one each for grades 1-3, 4-6, 7-9, and 10-12. Each section is laid out in three parallel columns, one for each grade. The guide is offset printed and staple-bound with a soft cover. OBJECTIVES AND ACTIVITIES: Both general objectives and specific behavioral objectives are listed at the beginning of each section. The main part of the section lists general activities and topics to be covered. Activities are not correlated with any specific objective. Instructional materials: No mention. STUDENT ASSESSMENT: No mention other than the behavioral objectives. OPTIONS: A one-page section at the end of the guide asks teachers to evaluate the guide as an aid to future revisions. (RT)
Educational level discussed: Elementary Education.
Educational level discussed: Grade 1.
Educational level discussed: Grade 10.
Educational level discussed: Grade 11.
Educational level discussed: Grade 12.
Educational level discussed: Grade 2.
Keywords: Curriculum Guides; Elementary Education; Grade 1.; Grade 10.; Grade 11.; Grade 12.; Grade 2.; Grade 3.; Grade 4.; Grade 5.; Grade 6.; Grade 7.; Grade 8.; Grade 9.; Language Arts; Secondary Education